International Conference on Optimization, Learning Algorithms and Applications: book of abstracts - Pereira, Ana I. (2021)
Welcome to OL2A 2021 - International Conference on Optimization, Learning Algorithms and Applications. OL2A offers a forum for the research community on optimization and learning to get together and share the latest developments and techniques as well as develop new paths and collaborations. OL2A provides a wide scope of presentations, covering many areas of optimiza- tion and learning and state of the art applications to multi-objective optimization, optimization for machine learning, machine learning for optimization, optimization and learning under uncertainty and 4th industrial revolution. It is with great pleasure that the Organizing Committee welcomes you all to OL2A 2021!